Labour productivity differentials within international companies - Pratten, C. F. (Cambridge : New York : Cambridge University Press, 1976)
This paper is a report on the first part of an enquiry to trace the reasons for differences in the performance of manufacturing industry in the UK and overseas by making systematic comparisons of the performance of companies.
Includes bibliographical references.
aia 20/03/2019
Loans
Keywords: International business enterprises; Labor productivity